“BIJ WIJZE VAN SPREKEN”: SPREEKWOORDEN IN HET IDIOLECT VAN VLADIMIR PUTIN ALS SPIEGEL VAN ZIJN BELEID - Dewaegenaere, Marie (Proverbium - Yearbook, 2017)
Russian President Vladimir Putin’s sharp-witted lapses into crass statements, juicy expressions, and vulgar references set the tone for his, to put it mildly, much-discussed and contentious leadership. His effective use of proverbs and folksy phrases shows us that proverbial language is part of his otherwise highly technocratic and bureaucratic style. This article discusses Putin’s use of proverbs, including the question how Putin demonstrated insight into the possibilities of proverbs to persuade the audience. In order to study the use and function of pro-verbs in Putin’s speech acts, a representative corpus with Putin’s proverbial statements was analyzed. By citing folksy bits of wisdom in his statements, Putin awakens pathos (emotion) in his audience to rouse them for his political agenda. His strategical use of accessible language adds a tinge of emotional pizzazz and reinforces the public perception of his ethos (authority). One could say that Putin, deploying a bountiful arsenal of proverbs, not unlike martial arts, exercises a kind of off-court verbal judo.